Informatics Training for Clinicians Is More Important than Hardware and Software - Safran, C. (Yearbook of Medical Informatics, 2009)
Objective The importance of training physicians and nurses in the art, skill and science of clinical informatics has never been greater. What level of training is necessary and sufficient to equip the 21st century healthcare workforce for the transformative opportunity enabled by widespread deployment of EHRs?Methods Building on the success of its 10x10 program, AMIA with support from the Robert Wood Johnson foundation took its next step to create the necessary documents to have clinical informatics recognized as a sub-specialty by the American Board of Medical Specialties (ABMS).ResultsWe defined the core content that had to be mastered and describing how physicians interested in the sub-specialty clinical informatics would be trained. The results of this work have been approved by the board of AMIA and have been published in its journal JAMIA.Conclusion The health challenges of the 21 century require that we rapidly train the clinical workforce in clinical informatics. In addition to buying hardware and software, our health systems need to sponsor this training. Two percent of every Health IT budget should be targeted for clinician education.
Keywords: Clinical informatics; training; EHR adoption; healthcare transformation